Perfectly Imperfect? The Barbie Film, Naomi Wolf’s Beauty Myth, and the Construction of Feminine Ideals - Febiola, Tsasa Vina; Susanti, Tia Ayu; Afifulloh, M ((JELE) Journal Of English Language and Education, 2024)
Barbie Movie has become a popular culture icon in the United States and worldwide. Barbie's live-action movie portrays Margot Robbie as a Barbie stereotype who is beloved, beautiful, and ideal. However, behind the glamour of Barbie's beautiful and perfect world, there is a deep-seated construct of American beauty standards, especially for girls and women's unrealistic expectations. This research examines the theoretical framework proposed by Naomi Wolf’s The Beauty Myth theory to explore how the Barbie film promotes and reinforces existing beauty standards in America. This study tried to analyze the Barbie film, identifying how Barbie's character constructs ideal beauty attributes so that the movie plays a role in influencing society's perspective on beauty standards, creating feelings of inferiority through the characters. This study provides a deeper understanding of how mass media and popular culture can influence perceptions of beauty by using qualitative methods to describe the data and Post-National American Studies as an approach to delve how movie is produced as a representation of American society. In addition, this study found that Barbie movie represents the beauty myth, such as physical perfection, eating disorders, and agelessness. At the same time, the narrative of the movie reflects a social critique of empowerment and stereotypes significantly for woman. Moreover, this film emphasizes that being a woman must meet various criteria, especially the typical white American woman as the world's standard of beauty.